Roundtable discussion reviews digital efficiency for global information literacy - Nor Salwana, Mohammad Idris (2022)
KUANTAN, 18 March 2022 – A total of 24 experts from all over the country participated in an online roundtable discussion on the efficiency of media literacy and information organised by Universiti Malaysia Pahang (UMP) in collaboration with the United Nations Educational Scientific and Cultural Organization (UNESCO) recently.